Bibliometric visualization analysis of gut-kidney axis from 2003 to 2022 - Ai, Sinan; Li, Yake; Tao, JiaYin; Zheng, Huijuan; Tian, Lei; Wang, Yaoxian; Wang, Zhen; Liu, Wei Jing (Frontiers in Physiology, 2023)
Background: The gut-kidney axis refers to the interaction between the gastrointestinal tract and the kidneys, and its disorders have become increasingly important in the development of kidney diseases. The aim of this study is to identify current research hotspots in the field of the gut-kidney axis from 2003 to 2022 and provide guidance for future research in this field. Methods: We collected relevant literature on the gut-kidney axis from the Web of Science Core Collection (WoSCC) database and conducted bibliometric and visualization analyses using biblioshiny in R-Studio and VOSviewer (version 1.6.16). Results: A total of 3900 documents were retrieved from the WoSCC database. The publications have shown rapid expansion since 2011, with the greatest research hotspot emerging due to the concept of the "intestinal-renal syndrome," first proposed by Meijers. The most relevant journals were in the field of diet and metabolism, such as Nutrients. The United States(USA) and China were the most influential countries, and the most active institute was the University of California San Diego. Journal co-citation analysis showed a strong tendency toward co-citation of research in the field of psychiatry. Author analysis revealed that Denise Mafra, Nosratola D. Vaziri, Fouque, and Denis made great contributions in different aspects of the field. Clustering analysis of the keywords found that important research priorities were "immunity," "inflammation," "metabolism," and "urinary toxin," reflecting the basis of research in the field. Current research frontiers in the field include "hyperuricemia", "gut microbiota", "diabetes", "trimethylamine n-oxide", "iga nephropathy", "acute kidney injury", "chronic kidney disease", "inflammation", all of which necessitate further investigation. Conclusion: This study presents a comprehensive bibliometric analysis and offers an up-to-date outlook on the research related to the gut-kidney axis, with a specific emphasis on the present state of intercommunication between gut microbiota and kidney diseases in this field. This perspective may assist researchers in selecting appropriate journals and partners, and help to gain a deeper understanding of the field's hotspots and frontiers, thereby promoting future research.